Dynamics and classification of RNA strands - Heng, Wang Cong (2017)
The Ribonucleic Acid (RNA) with pseudoknots folding problem is formulated as an N × N matrix ﬁeld theory and this formalism allows the terms in the partition function to be classiﬁed using a topological variable namely the Topological Genus. When N is large, the relationship between the genus and RNA with pseudoknots is found to be closely related to the Feynman diagrams of Quantum Field theory. This allows the classiﬁcation of RNA according to this topological genus. There are diﬀerent ways to represent the RNA with pseudoknots and the genus of the RNA can be calculated using the double line representation numerically. Hence a numerical code is developed to generate the genus given the base-pairing and respective dot-parenthesis information